(untitled) (International Journal of Mathematics and Physics, 2016)
The article shows investigations of anisotropy of high energy cosmic rays.We calculated the number of cosmic rays (events) of extremely high energies with different threshold energy, the direction of arrival of which lies on the angular distances from the active galactic nuclei, not large than given. Similar calculations were also carried with maximum of one hundred numerical experiments of concentrating around active galactic nuclei isotropic distribution of particles. For interval to 30 in all cases, except for a local minimum at 20 for distance <100 Mpc, these values were less than the observed in real distribution. Thus, our results indicate a clear correlation between the arrival directions of cosmic rays of extremely high energy and direction to close (within 100 Mpc) to the solar system active galactic nuclei, therefore, these objects are one of the real sources of such particles. G M T Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Звуковая функция ограничена 200 символами Настройки : История : Обратная связь : Donate Закрыть